APPROACHES FOR COCOA PROCESSORS TO ADAPT FOR SUSTAINABLE SURVIVAL IN THE SOUTHERN PROVINCES OF THAILAND - Chanthaen, Wachiraporn; Bhaibulaya, Pawitpol (Journal of MCU Nakhondhat, 2025)
The objectives of this research are: 1) Study the perception of problems that are a worldwide phenomenon facing cocoa processing enterprises in the southern provinces of Thailand. 2) Study the innovative management and adaptation of cocoa processing enterprises for sustainable survival in the southern provinces of Thailand. 3) Find ways to adapt for the sustainable survival of cocoa processing enterprises in the southern provinces of Thailand. The sample groups used were farmers, and executives of cocoa processing enterprises academics with knowledge and expertise in product development for sustainable survival. The qualitative researcher used a random sampling method of key informants, selecting experts using the purposive sampling technique. The research results found that entrepreneurs are aware of the country’s climate problems of the country, both in terms of temperature and rainfall directly affect cocoa processing operators because cocoa is a plant that is quite sensitive to weather conditions. It needs consistent temperatures, high humidity, lots of rain, and soil with a high nitrogen content. Therefore, when the weather changes, it affects the quality. And the amount of cocoa beans for the sustainable survival of cocoa processing enterprises in the southern provinces of Thailand. Research is needed. Develop innovation, and technology, and raise the quality management of Thai products in every cocoa business unit from upstream, midstream, and downstream, along with developing the quality of cocoa beans and products from Thai cocoa. The government should help invest in technology and research and development, investing in modern technology and research and development to create new innovations. It is an important factor that will help drive the business towards sustainability. Budgets and resources should be established to support R&D projects related to production, processing, and marketing.